2021
DOI: 10.1002/bse.2772
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis: Did green supply chain management alleviate the effects of COVID‐19?

Abstract: Supply chain management played a central role during the COVID-19 crisis, as the outbreak of the pandemic disrupted the majority of all global supply chains. This paper tests whether companies that use green supply chain management (GSCM) practices benefited from a buffer effect in the context of COVID-19. Our empirical analysis, conducted on a sample of U.S. companies, shows that GSCM companies experienced less negative abnormal stock returns during the crisis. This result contributes to the literature on fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 49 publications
2
43
1
1
Order By: Relevance
“…During the same period, Dow Jones, FTSE 100, DAX, NIKKEI 225, Shanghai and BIST 100 lost value by 34%, 34%, 35%, 27%, 14% and 29%, respectively (Bloomberg, 2008 ). Moreover, the rise in the Chicago Board Options Exchange Volatility Index (CBOE VIX), which is considered as one of the leading indicators of the business cycles and which reflects the volatility in global markets, was very close to the value it had assumed in the 2008 global financial crisis (Fasan et al, 2021 ; Just & Krzysztof, 2020 ; Salisu & Akanni, 2020 ). The CBOE VIX value, which reached 80 points during the 2008 global financial crisis, reached the same level at the end of March 2020 (see Figure 1 ).…”
Section: A Literature Review and The Variable Selectionmentioning
confidence: 82%
“…During the same period, Dow Jones, FTSE 100, DAX, NIKKEI 225, Shanghai and BIST 100 lost value by 34%, 34%, 35%, 27%, 14% and 29%, respectively (Bloomberg, 2008 ). Moreover, the rise in the Chicago Board Options Exchange Volatility Index (CBOE VIX), which is considered as one of the leading indicators of the business cycles and which reflects the volatility in global markets, was very close to the value it had assumed in the 2008 global financial crisis (Fasan et al, 2021 ; Just & Krzysztof, 2020 ; Salisu & Akanni, 2020 ). The CBOE VIX value, which reached 80 points during the 2008 global financial crisis, reached the same level at the end of March 2020 (see Figure 1 ).…”
Section: A Literature Review and The Variable Selectionmentioning
confidence: 82%
“…Furthermore, 33 barriers were identified in innovations for sustainable SCM in the manufacturing industry of a developing country, and a framework to overcome these barriers was provided by using the best–worst method (Gupta et al 2020 ). However, Fasan et al ( 2021 ) reported that companies with green SCM practices experienced less negative abnormal stock returns during the pandemic. They suggested that green SCM is identified as an effective risk management tool.…”
Section: Emerging Research Themes Of Ai and Supply Chain Resiliencymentioning
confidence: 99%
“…According to the efficient market hypothesis of Eugene F. Fama, all valuable information can be precisely and timely reflected through the stock price [38]. In this way, we can observe stock price fluctuations during the event window to analyze the influence of the event, just as many studies already have done in investigating how the outbreak of events influence firm value [39][40][41]. The DiD methodology avoids endogeneity raised by reverse causality and omitted variables.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous literature [41], we conducted the event study and measured firm value by calculating the cumulative abnormal return (CAR) and abnormal return (AR) surrounding the event of the "4 + 7" procurement policy. The measurement includes the following steps.…”
Section: Firm Valuementioning
confidence: 99%